The Effect of Low Level Laser Therapy on Direct Pulp Capping in Dogs - Bidar, Maryam; Moushekhian, Siavash; Gharechahi, Maryam; Talati, Ali; Ahrari, Farzaneh; Boujarpour, Maryam (Journal of Lasers in Medical Sciences, 2016)
Introduction: The aim of this study was to determine the histologic effect of low level laser therapy (LLLT) with or without the use of mineral trioxide aggregate (MTA) on exposed pulp tissues of dogs. Methods: Twenty-five premolar teeth in three healthy mature dogs were randomly divided into five groups. In group 1, the pulp tissue was capped with MTA. In groups 2 and 3, before capping with MTA, the exposure site was irradiated by low power lasers at 630 nm (20 mW, 150 seconds, 7.5 J/cm2) and 810 nm (peak power 80 W, average power 50 mW, 1500 Hz, 50 seconds, 6.25 J/cm2) wavelengths, respectively. In groups 4 and 5, the exposure site was irradiated similar to that described in groups 2 and 3, but the pulp tissue was covered by gold foil instead of MTA. After 2 months, the animals were sacrificed and the samples were prepared for histologic evaluation. Results: There were differences in pulpal response and dentinal barrier formation among the study groups. The morphology of pulpal tissue and the integrity of dentinal barrier and formation of odontoblastic layer were more favorable in the first three groups. The occurrence of extensive and intense inflammation and necrosis was more frequent in groups 4 and 5. Conclusion: Under the conditions used in this study, the presence of MTA as a pulp capping material was more important than laser therapy in the success of direct pulp capping (DPC) treatment. MTA proved to be an effective material either alone or in combination with laser irradiation in vital pulp therapy.